Motivational Interviewing in Primary Care and General Health Care Settings: a Meta-Analysis - (:unkn) unknown (My University, 2015)
The rate of mortality and morbidity due to alcohol consumption warrants a comprehensive and evidence-based investigation exploring the efficacy of behavioral interventions within a general health care setting as a means of alcohol reduction. A particular type of intervention, known as Motivational Interviewing (MI; Miller, 1983) and Motivational Enhancement Therapy (MET; Miller, Sovereign, & Krege, 1988), both of which have seen surge in popularity, merits further inspection. Through electronic database searching, hand searching previous meta-analyses and systematic reviews, and searching the Motivational Network of Trainers bibliographic resource, 33 randomized controlled trials were located isolating the effect of motivational interviewing in general health care settings. The average effect (d = .153, k = 33, N = 32,588) constitutes a small effect in favor of MI and/or MET, with no substantial benefit in offering MET (d = .125, (95% CI [0.044, 0.206], N = 21,226) as opposed to MI (d = .114, (95% CI [0.06, 0.016], N = 8689). MI and/or MET produces a small benefit within primary care and is relatively comparable to other brief interventions within the same setting. Primary care providers wishing to implement MI/MET within their practice may be reasonably assured that MI/MET will be more effective in improving patient outcomes than delivering no intervention.
Keywords: Alcohol; Meta-Analysis; Motivational Interviewing; Primary Health Care